Prenatal PM2.5 exposure and its association with Neurodevelopmental impairment in children: a narrative review - Amy Azira Hamis; Muhammad Al-Amin Shaharuddin; Nazmeen Adline Fawwazah A Fauzi; Mohd Rizal Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2023)
Air pollutants, including PM2.5, are an increasing threat to public health. Studies have reported the adverse effect of PM2.5 exposures during pregnancy on neurodevelopment in children. We performed a narrative review using the PubMed, Web of Science, and Scopus databases from 2017 to 2022 using keywords such as prenatal, particulate matter, neurodevelopment, and children. This review aims to identify symptoms of impaired neurodevelopment in children associated with prenatal PM2.5 exposure, the association between the timing of prenatal exposure PM2.5 and symptoms of impaired neurodevelopment in children as well as other factors that may influence the association of prenatal PM2.5 exposure and symptoms of impaired neurodevelopment in children. A total of 25 articles were included in this review. Symptoms of neurodevelopmental impairment associated with prenatal exposure to PM2.5 include language, speech, and communication symptoms; motor skills; behaviour and social skills; memory as well as learning/cognitive symptoms. Neurodevelopmental impairments were associated with exposure to PM2.5 across all three trimesters with impairment in communication and behavioural domains predominating in those exposed during the first trimester. Generally, males were more susceptible to having neurodevelopmental impairment symptoms compared to females. More information regarding the effect of prenatal PM2.5 exposure on neurodevelopmental domains of children will support public health policies that reduce air pollution and improve children’s health.